Apple Black. 1, Neo freedom - Oguguo, Odunze (Oguguo, Odunze. Apple Black, 2022)
"Apple Black follows the young sorcerer Sano as he struggles to fulfill his prophesied destiny as savior of the world known as the Trinity"--